2009
DOI: 10.2215/cjn.04750908
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Antagonists for Preventing the Progression of Chronic Kidney Disease

Abstract: Background and objectives: Addition of aldosterone antagonists (AA) might provide renal benefits to proteinuric chronic kidney disease (CKD) patients over and above the inhibition of renin-angiotensin system blockers (RAS). We evaluated the benefits and harms of adding selective and nonselective AA in CKD patients already on RAS.Design, setting, participants, & measurements: MEDLINE, EMBASE, and Renal Health Library were searched for relevant randomized clinical trials in adult CKD patients. Results were summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(148 citation statements)
references
References 42 publications
6
133
0
9
Order By: Relevance
“…1). The selective aldosterone blocker eplerenone also ameliorates podocyte injury, proteinuria and salt-evoked nephropathy [30,31].…”
Section: Commonly Prescribed Drugs Directly Targeting the Podocytementioning
confidence: 99%
“…1). The selective aldosterone blocker eplerenone also ameliorates podocyte injury, proteinuria and salt-evoked nephropathy [30,31].…”
Section: Commonly Prescribed Drugs Directly Targeting the Podocytementioning
confidence: 99%
“…The number of patients in the study was low, but the study was strong to show that spironolactone can reduce proteinuria in a short-duration (23). In 2009, Navaneethan and colleagues in a systematic review about the prevention of progression of kidney disease with aldosterone antagonists using Medline data base concluded that in patients who received ACEi or ARB, aldosterone antagonists reduced proteinuria, although the risk of hyperkalemia increased (24). In 2008, Bomback and colleagues in a systematic review showed that most studies about spironolactone have these characteristics in common: CKD with different causes, Low number of patients studied (less than 30), mean of GFR > 60 and potassium cutoff equal to 5.5.…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks after discontinuation of spironolactone, proteinuria returned to its initial level. The level of proteinuria was directly related to the level of aldosterone (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Accumulating evidence shows that Ald, an end product of that system, plays a key role in the progression of chronic kidney disease (CKD) due to salt-sensitive hypertension, [2][3][4] and that mineralocorticoid receptor (MR) blockers, which inhibit the injurious effect of Ald on the kidney, contribute to a reduction in albuminuria and proteinuria in CKD patients. 5,6 MR blockers are therefore considered to play a crucial role in preventing the progression of CKD with hypertension. However, treatment with MR blockers can induce hyperkalemia, which is a concern in patients with renal dysfunction and requires caution in prescribing MR blockers for advanced CKD patients.…”
Section: Introductionmentioning
confidence: 99%